Effect of catalyst carbon supports on the oxygen reduction reaction in alkaline media: a comparative study. Issue 97 (4th October 2016) - Molina-García, Miguel A.; Rees, Neil V.
Abstract : Four common catalyst carbon supports are quantitatively compared in an integrated study towards the oxygen reduction reaction in alkaline media. Abstract : Some carbon materials commonly used as electronically-conductive supports for catalysts in fuel cell research are Carbon Black (CB), multi-walled carbon nanotubes (MWCNT), Graphene Oxide (GO) and reduced graphene oxide (rGO). Here we present a comparative study into the relative effects of each of these on the performance towards the oxygen reduction reaction (ORR) in alkaline media. For the purposes of comparing the supports, a simple Pt catalyst is used and the performance is evaluated via Koutecky–Levich analysis and direct measurement of peroxide by rotating ring-disk electrode (RRDE) to determine the number of electrons ( n ) transferred in the ORR. It is found that Pt/CB follows a quasi 4-electron mechanism due to that the ORR takes place mainly on the active Pt particles, whereas Pt/MWCNT, Pt/GO and Pt/rGO exhibit a mixed behaviour between the two proposed mechanisms due to the higher activity of the graphene-derived supports towards the peroxide formation compared to CB. The effect of the oxide groups of GO and the metal impurities of MWCNT on the catalytic performance is also studied.